LEARNING ENGLISH USING SONGS FOR ELEMENTARY STUDENTS AT KAVLING SEROJA - Sulastri Manurung; Dewi Yana (Universitas Riau Kepulauan, 2018)
Learning English for Elementary Students is different with Junior High School or Senior High School Students. It is due to the characteristic and learning style of children differ from adolescents and adults. Therefore, learning should be well-designed and concern the students’ characteristics and ages. The program was carried out to help elementary students in RW 16 Kavling Seroja to overcome the problems they faced in learning English which is often faced with the rules and form of the language in their learning. Learning activity was conducted by using songs related to the subject matter and concern their age. Learning was conducted every Saturday and Sunday for two months. The use of song in English learning can be considered as best tool because in addition to motivating students in learning, fostering fun atmosphere in learning, this activity is also useful in developing students’ vocabulary, listening skills and pronunciation. Songs can be used in different in learning the four aspects of English including listening, reading, speaking, and writing. The results of the implementation of this program in RW 16 Kavling Seroja gained positive responses from the students. It is proven by the students’ enthusiasm during the learning activity, the improvement of students’ motivation in learning, as well as the improvement of students’ English skills in the aspect of pronunciation, vocabulary, reading, and listening.